A Near-Infrared-Emissive Alkynyl-Protected Au24 Nanocluster - Wan, Xian-Kai; Xu, Wen Wu; Yuan, Shang-Fu; Gao, Yi; Zeng, Xiao-Cheng; Wang, Quan-Ming (Angewandte Chemie International Edition, 2015)
An alkynyl‐protected gold nanocluster [Au24(CCPh)14(PPh3)4](SbF6)2 has been prepared by a direct reduction method. Single‐crystal X‐ray diffraction reveals that the molecular structure contains a Au22 core that is made of two Au13‐centered cuboctahedra that share a square face. Two staple‐like PhCCAuCCPh motifs are located around the center of the rod‐like Au22 core. This Au24 nanocluster is highly emissive in the near‐infrared region with λmax=925 nm and the nature of the HOMO–LUMO transition is investigated by time‐dependent DFT calculations. Good as gold: An alkynyl‐protected gold nanocluster [Au24(CCPh)14(PPh3)4](SbF6)2 is reported which contains a Au22 core composed of two Au13 centered cuboctahedra that share a square face. Two staple‐like PhCCAuCCPh motifs are located around the center of the rod‐like Au22 core. The Au24 nanocluster is highly emissive in the near‐infrared region (λmax=925 nm). Atom colors: Au=orange; C=gray.